Shifting the burden of proof in doping: lessons from environmental sustainability applied to high-performance sport - Camporesi, S.; Knuckles, J. A. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
In this paper, we analyse the role of incentives in high-performance sports, borrowing concepts from sustainability policies and applying them to the context of doping in sports. Professional athletes discount their future health in exchange for desired enhanced performances. In the same way, many industrialised societies discount future environmental health for short-term economic returns, jeopardising the future of the planet. We propose a solution to alter this discounting, by applying the lessons from environmental sustainability, which has long proposed shifting the burden of proof away from regulators in order to alter the practice of discounting the planet's future health for current economic gains, to high-performance sports. We argue that the burden of proof for doping should not rest on the athlete or the team of sports doctors, but should rest instead on the sponsors. Under this system, WADA would retain and strengthen its own testing, and impose severe penalties on the sponsors of any athlete found to be doping. Only by making the companies accountable for the athletes they sponsor, can we de-link sponsorship money from a win-at-all-costs mentality in sports that in turn leads to doping, and subsequently to discounting the future health of the athlete.